Mapping the Landscape of Sustainability Literacy Research in Vocational Education: A Bibliometric Analysis - Destie Monikha Austriya Umbara; Mustika Nuramalia Handayani (Journal of Vocational Education Studies, 2023)
Integrating sustainability literacy into vocational education is vital for preparing students to tackle 21st-century sustainability challenges. This study conducts a comprehensive bibliometric analysis to map existing literature on sustainability literacy in vocational education, revealing trends, gaps, and themes. Using the Systematic Literature Network Analysis (SLNA) approach, it combines bibliometrics with systematic literature review (SLR). The customized SLR process identifies relevant Scopus articles from 2018 to 2023 with specific keywords. The analysis identifies eight main topic clusters, including environmental literacy as a key theme. Other clusters cover sustainability literacy, education approaches, vocational training, higher education, and country-specific case studies. The study indicates growing interest in sustainability literacy, seen in the rising publications since 2017. The findings emphasize the need for targeted pedagogical strategies and a more cohesive research landscape to enhance sustainability literacy's impact in vocational education. This research serves two purposes it offers insights into current trends, and inform about the importance of sustainability literacy in vocational education and how it can be implemented. In conclusion, this analysis provides a comprehensive view of sustainability literacy research in vocational education, guiding researchers, policymakers, and educators to improve sustainability education and ready students for sustainability-focused industries.